Penerapan Metode Ilhamqu dalam Menghafal Al-Qur’an Santri di Pondok Pesantren Assalafie Babakan Ciwaringin Cirebon - Agus Mahrus, Nanang; Rubiyad, Adib (SETYAKI : Jurnal Studi Keagamaan Islam, 2023)
This research aims to determine the implementation of the Ilhamqu method in the process of memorizing the Quran by students at Assalafie Islamic Boarding School in Babakan Ciwaringin Cirebon. The research approach used is descriptive qualitative with a field research method. Data collection techniques used include observation, interviews, and documentation. Meanwhile, for data analysis, the Milles and Huberman model method is used which involves data reduction, data presentation, and conclusion. The Ilhamqu method is an approach to memorizing the Quran that combines various types of intelligence and utilizes the senses of hearing, sight, speech, and movement. This approach uses a pattern of mutual attention and matching to achieve optimal memorization results. At Assalafie Islamic Boarding School in Babakan Ciwaringin Cirebon, the implementation of the Ilhamqu method involves several steps. First, new students are required to read the Quran a maximum of 20 times or a minimum of 10 times using the Bin-Nadzar method. Second, before starting the memorization process, each student must have a partner who aims to match and motivate each other, as well as listen to each other's memorization. Third, in the deposit phase, students must visit the mentor after consulting with their partner. The purpose of this consultation is to enable them to listen to each other's memorization before presenting it to the mentor.